Analysis of Differential Proteins in Two Wing-Type Females of Sogatella furcifera (Hemiptera: Delphacidae). Issue 1 (4th April 2016) - Liang, Zi-Qiang; Song, Shao-Yun; Liang, Shi-Ke; Wang, Fang-Hai
Abstract: Sogatella furcifera (Horvath) is an important rice pest with the wing dimorphism, including macropterous and brachypterous morphs. The protein expression profiles in two wing-type adults and two wing-type disc fifth-instar nymphs were analyzed using two-dimensional gel protein electrophoresis and mass spectrometry. In adults and fifth-instar nymphs, 127 and 162 protein spots were detected, respectively. Fifty-five differentially expressed protein spots were identified between the long-winged adults and the short-winged adults, and 62 differentially expressed protein spots were found between the long-winged disc fifth-instar nymphs and short-winged disc fifth-instar nymphs. In long-winged and short-winged adults, six and seven specific protein spots were identified, respectively, with five and seven protein spots having more than threefold increased level, respectively. In long-winged and short-winged disc morph nymphs, 8 and 12 specific protein spots were identified, respectively, with 11 and 17 spots containing more than threefold increased level, respectively. Among the 16 identified proteins, five proteins are associated with muscle function, suggesting that muscle is a main tissue where the genes were differentially expressed between the two wing types. In addition, the content of a peptidase with an insulinase domain was higher (by 3.02 ± 0.59 fold) in the short-winged fifth-instar nymphs than in the long-winged fifth-instar nymphs, which suggests that this peptidase may be involved in wing differentiation by regulating insulin receptors. The results of this study provide some genetic clues for the wing differential development in S. furcifera and provide more references for future studies.